Study of Correlation of Severity of Hepatic Cirrhosis with Severity of Bone Changes Measured by BMD (Bone Mineral Density) - Alam, Md Ashraful; Ahmed, Nooruddin; Alam, Sahinul; Mahtab, Mamun Al (Bangladesh Journal of Medicine, 2013)
Background & Aim Metabolic bone disease is common among patients with chronic liver disease and still it is underestimated complication in liver cirrhosis. The prevalence and presentation of bone disease in chronic liver diseases have been poorly described except for cholestatic liver diseases. This study aims at evaluation of the prevalence and degree of bone changes in patients with cirrhosis and to correlate severity of hepatic cirrhosis with the severity of bone changes. Patients and Methods Bone mineral density (BMD) was studied using dual energy X-ray absorptiometry (DEXA) in 60 subjects of 15-45 years old. Of them 30 subjects are patients with liver cirrhosis and rest of the 30 subjects were control group without having liver disease or any other chronic disease. The diagnosis of cirrhosis was based on clinical, biochemical, and ultrasonographic findings. Patients with renal impairment, cholestatic liver disease, chronic lung disease, prolonged bed ridden patients or deformity of spine, pelvis or wrist were excluded from the study. Results of BMD were then correlated with the Child score. Results Eighteen (60%) patients had decreased bone mineral density (BMD). Of which 15 (50%) patients have got osteopenia and 3 (10%) patients have got osteoporosis. No correlation was found between the T-score and Child Paugh score (p =0.236). Significant correlations were found between BMD and serum bilirubin. Conclusion Liver cirrhosis is a risk factor for the development of bone loss and there is a high prevalence of BMD disorders in cirrhotic patients. The severity of bone loss is not related to the severity of liver disease. Hyperbilirubinemia and low albumin is a contributing factor to altered bone mineral density in patients with liver cirrhosis DOI: http://dx.doi.org/10.3329/bjmed.v22i2.13588 Bangladesh J Medicine 2011; 22: 41-46